Bronchiectasis following treatment for high‐risk neuroblastoma: A case series. Issue 10 (10th March 2017) - Adams, Madeleine; Traunecker, Heidi; Doull, Iolo; Cox, Rachel
Abstract: High‐risk (HR) neuroblastoma remains a very challenging disease to treat and long‐term cure is only possible with intensive, multimodal treatment including chemotherapy, high‐dose therapy, radiotherapy, surgery, and immunotherapy. As a result, treatment‐related morbidity and late effects are common in survivors. This report outlines a case series of six patients who developed a chronic productive cough following treatment for HR neuroblastoma. High‐resolution computed tomography scanning confirmed the diagnosis of bronchiectasis. Two of the patients who have undergone immunological testing demonstrate hypogammaglobulinaemia and impaired vaccine response. Persistent cough in patients treated for neuroblastoma warrants investigation and consideration of immunological referral.